Biomechanical and Microstructural Benefits of Physical Exercise Associated With Risedronate in Bones of Ovariectomized Rats - Shimano, Roberta Carminati; Macedo, Ana Paula; Falcai, Mauricio Jose; Ervolino, Edilson [UNESP]; Shimano, Antonio Carlos; Mardegan Issa, Joao Paulo (Wiley-Blackwell, 2014)
Several treatments have been developed aiming the prevention of bone loss. There are discussions about the best prophylactic and therapeutic procedures for osteoporosis. This study evaluated the effects of physical exercise associated with risedronate as a prophylactic and therapeutic procedure in osteopenic bones of rats submitted to ovariectomy. We used 48 Wistar rats divided into: ovariectomized or subjected to sham surgery. Ovariectomized rats were divided into the following sub-groups: OVX, 12 weeks sedentary; OVX-EX, treadmill training for 12 weeks; OVX-RA, 12 weeks with risedronate administration; and OVX-EX-RA, 12 weeks with risedronate administration and treadmill training. Rats subjected to sham surgery were divided into the following sub-groups: SH, 12 weeks sedentary; SH-EX, treadmill training for 12 weeks; SH-RA, 12 weeks with risedronate administration; and SH-EX-RA, 12 weeks with risedronate administration and training on the treadmill. The effectiveness of the treatment was evaluated in tibias using biomechanical, radiological, histomorphometric, and immunohistochemical analyses. Data were analyzed by statistical tests, with significance level of P < 0.05. Results of mechanical tests showed that the SH-RA group had lower values compared with OVX-RA group; densitometry showed no significant differences; according to histomorphometric methods, OVX group presented lower results than the SH-EX, OVX-RA, SH-EX-RA, and OVX-EX-RA groups, and SH-EX-RA and OVX-EX-RA groups showed values higher than SH-RA, SH, and OVX-EX groups. The SH-EX-RA and OVX-EX-RA groups had decreased immunostaining for tartrate-resistant acid phosphatase and receptor activator of nuclear factor kappa-B ligand and increased osteoprotegerin immunostaining. In this experimental model, it was concluded that the physical training associated with use of risedronate exerted positive effects on biomechanical and microstructural properties in bones of ovariectomized rats. (C) 2014 Wiley Periodicals, Inc.
Keywords: bone diseases; metabolic; medicine; microscopy; physical exercise